Implementasi Pembelajaran PjBL Berdifferensiasi Untuk Mengembangkan Berpikir Kreatif Siswa Dalam Merancang Pembangkit Tenaga Listrik Melalui Canva Pada Siswa Sekolah Dasar - Zulkifli, Arif; Sudarti; Prihandono, Trapsilo (Universitas Pendidikan Ganesha, 2025)
The results of the 2022 International Student Assessment (PISA) indicate that Indonesian students' creativity still requires serious attention. Therefore, this study aims to examine the implementation of differentiated PjBL learning to develop students' creative thinking skills in designing a power plant using Canva in elementary school students. This research was conducted experimentally using a